A Review of ICT Integration in Agricultural Extension Services. A Global Perspective - Byamukama, Willbroad; Ssemakula, Edward; Ssekandi, Joesph; Arinda, Shaman; Businge, Phelix; Kalibwani, Rebecca; Atukunda, Christian; Turyasingura, Benson (East African Journal of Interdisciplinary Studies, 2025)
The integration of Information and Communication Technologies (ICT) in agricultural extension services is transforming knowledge dissemination, addressing challenges of accessibility, efficiency, and inclusiveness. Traditional extension systems, constrained by resource limitations and outdated methods, struggle to meet modern agricultural demands. ICT tools such as mobile phones, internet-based platforms, Geographic Information Systems (GIS), drones, Artificial Intelligence (AI), and blockchain provide real-time, localised, and cost-effective solutions. This review examines the impact of ICT in enhancing agricultural extension services, highlighting initiatives like India’s mKisan, Africa’s e-Agriculture programs, and the global Digital Green initiative. These platforms have improved access to timely information on weather, pest management, and market trends, boosting productivity and resilience. However, several barriers hinder ICT adoption, including the digital divide, limited smartphone and internet access, unreliable electricity, and socioeconomic inequalities, particularly affecting women and marginalised groups. Low digital literacy, inadequate infrastructure, and weak policy support further constrain scalability. Addressing these challenges requires investments in rural connectivity, affordable technology, and capacity-building initiatives. Public private partnerships, ICT funding, and participatory, farmer-centred approaches are crucial for long-term success. Future prospects include AI-driven predictive analytics, blockchain for transparent supply chains, and augmented/virtual reality for training.